Diagnostic Performance of Atherosclerotic Carotid Plaque Neovascularization with Contrast-Enhanced Ultrasound: A Meta-Analysis. (7th March 2022) - Dong, Shanshan; Hou, Jianzhong; Zhang, Caiyun; Lu, Guilin; Qin, Wenjuan; Huang, Lei; Zhou, Guangqin
Abstract : Objectives . To evaluate the diagnostic performance of contrast-enhanced ultrasound (CEUS) for atherosclerotic carotid plaque neovascularization. Methods . The electronic databases like PubMed, Embase, OVID, and Web of Science were used to search for the relevant studies, which are involved in the evaluation of the diagnostic parameters of QUS for atherosclerotic carotid plaque neovascularization. Review Manager 5.4 and Stata 14.0 were used to estimate the pooled diagnostic value of CEUS. Forest plots, sensitivity analysis, and Deeks' funnel plots were performed on the included studies. Results . Ten studies eventually met the final inclusion criteria. For diagnostic performance, CUES showed that the pooled values of sensitivity, specificity, positive likelihood odds ratios, negative likelihood odds ratios, and diagnostic odds ratios were 0.83 (95% CI 0.78-0.86), 0.77 (95% CI 0.68-0.84), 3.61 (95% CI 2.59-5.03), 0.23 (95% CI 0.18-0.28), and 16.02 (95% CI 10.02-25.60), respectively. The estimate of the area under curve (AUC) was 0.85 (95% CI 0.82-0.88). Conclusion . Our research supported that CEUS had high sensitivity and specificity in the diagnosis of atherosclerotic carotid plaque neovascularization. More high-quality prospective multicenter studies focusing on the accuracy of CEUS for carotid atherosclerotic plaque should be performed to verify our conclusions.